Studying crystal-field splitting difference of Eu3+ ions from orthorhombic to cubic Ca4Al6SO16. Issue 5 (1st April 2020) - Zhang, Jinpu; Wu, Jiaming; Lu, Xiaolei; Ma, Shuwei; Lei, Tianyu; Wang, Shuxian; Ye, Zhengmao; Cheng, Xin
Abstract: Eu 3+ lanthanide ion possesses abundant 4f-4f transition lines in the visible spectral region, and its spectroscopic changes can sensitively reflect the variation of local ligand environments. Here, Eu 3+ ions are successfully introduced into Ca4 Al6 SO16 lattice, and the structural difference from orthorhombic ( o -Ca4 Al6 SO16 ) to cubic ( c -Ca4 Al6 SO16 ) phases is systematically analyzed. On that basis, the related influence on crystal-field splitting of Eu 3+ ions is discussed in detail. The obtained results indicate that Eu: o -Ca4 Al6 SO16 and Eu: c -Ca4 Al6 SO16 have three and two non-degenerate 5 D0 → 7 F0 transition peaks, respectively. Through the theoretical analysis and low-temperature (78 K) luminescent investigation with changing the excitation wavelength, those non-equivalent Ca 2+ sites are assigned as o -Ca(1) ( 577.6 nm), o -Ca(3) ( 579.6 nm), o -Ca(4) ( 580.6 nm), c -Ca(1) ( 578.7 nm), and c -Ca(2) ( 580.2 nm), respectively. In addition, with the increase of c -Ca4 Al6 SO16 content in the sintered product, the fluorescence intensity ratios of I 580.6 / I 613.7, I 616.2 / I 613.7 and I 621 / I 613.7 present a gradual decreasing tendency. And, the introduction of c -Ca4 Al6 SO16 into the as-prepared product is beneficial for increasing the decay lifetime of the 5 D0 excited state and enhancing the resistance capability to thermally induced fluorescence quenching. What discussed in this work might provide some useful thoughts for multi-phase studies and broaden the application range of lanthanide fluorescent probes.